Unsur-Unsur Budaya Dalam Legenda Upacara Adat Mandhasiya Di Pancot Karanganyar: Tinjauan Antropologi Sastra Dan Relevansinya Dalam Pembelajaran Sastra Di Sekolah Menengah Atas - Suwanti, Alfina Ari, Dr. Nafron Hasyim (2016)
The aims of this research are describing (1) the structural aspect that builds the legend of Mandhasiya, (2) the cultural elements in the legend of Mandhasiya, and (3) the result relevancy of the research aiming to implement it in the Literature subject in teaching and learning process in Senior High School (SMA). This research belonged to the qualitative descriptive research. The data of this research are paragraphs of the Mandhasiya legend itself, while the data sources in this research is the resource person as the primary data and the other documents as the secondary data source. The data collecting technique used in this research were the technique of in-depth interviews, observation, documentation and combination. The triangulation data was used as the technique of data validation while the data analysis technique used in this research was the dialectics. The results of this research are (1) the legend of Mandhasiya had some element of builders, those elements are facts (there are 7 characters, flashback, and the social background in the past) and idea of the darkness beaten by good values; (2) there were four elements of universal culture, those four elements are the system of religion and religious ceremony, people of Pancot village believed that there were such an esoteric wisdom and the truth of the legend by the existence of Watu Gilang; the system of Social organization, the existence of a kingdom with its people and king; the performance of reyog; and the society livelihood system which are mostly the farmer of onion, garlic and carrot; and (3) this research was relevant with teaching and learning process of Literature subject in X grade the second semester in accordance with the decree of SK 13 KD 13.1 and 13.2 for the KTSP and the XII grade 1 st semester relating to historical stories to the Kurikulum 2013. Keywords: the cultural elements, the implementation of literary study, the legend.